A market inventory of construction wood for residential building in Europe – in the light of the Green Deal and new circular economy ambitions. (March 2023) - Sikkema, R.; Styles, D.; Jonsson, R.; Tobin, B.; Byrne, K.A.
Highlights: Country level data on European wood use to assess wood for construction intensity. Six countries have construction wood markets in the introduction phase. Twelve countries are in the growth phase of the BCG matrix, with a ratio larger than 0.10 (m 3 m −2 ). Eight countries are classified as having a mature stage construction wood market. Two countries classified as having wood for construction in the decline phase. Abstract: Wood is an energy efficient, low carbon construction material that if carefully managed can contribute significantly to European climate policy goals in urban environments. The aim of this study is to assess the current construction wood use intensity the ratio of apparent national consumption of wood for construction (in m 3 ) to the useful floor area of newly finished dwellings (in m 2 ) and to identify when and where additional policy measures are required. Results show that Cyprus/Malta have the smallest use with a ratio of 0.01, Estonia/Romania the greatest use with a ratio of 0.32. The need for additional policy measures, was assessed using the Boston Consultancy Group (BCG) matrix with four product development phases, based on the aforementioned ratio versus future growth. Six, twelve, eight and two countries are in the "Introduction", "Growth", "Maturity" and "Decline" phases, respectively. At the EU level, the European Commission should consider introducing a Renewable Material Directive, in which a Non-biogenic Material Comparator shows the average GHG substitution effect of using wood for construction. At the international level, a new harvested wood product (HWP) category in the IPCC Guidelines is recommended for construction wood with a longer lifespan than the current HWP categories.